Prevalence of metabolic syndrome in ankylosing spondylitis: a multi national meta-analysis study - Sandeep Samethadka Nayak; Kwame Boateng Agyeman; Khushbu Viresh Janani; Maryam Jafari; Mohammad Amouzadeh Lichahi; Pubali Biswas; Mohammad Hashemi; Nimra Shafi; Yasmin Sahli; Ehsan Amini-Salehi; Narsimha Rao Keetha (Diabetology & Metabolic Syndrome)
Abstract Background Ankylosing spondylitis (AS) is a chronic inflammatory disease associated with an increased risk of metabolic syndrome (MetS), a cluster of cardiometabolic risk factors. However, the prevalence of MetS in AS remains uncertain. This meta-analysis estimates the global prevalence of MetS in AS patients and identifies factors contributing to its variability. Methods A systematic search of PubMed, Scopus, Embase, and Web of Science was conducted for studies published up to January 18, 2024. A random-effects model was used to estimate pooled prevalence, while meta-regression and subgroup analyses explored sources of heterogeneity. Results Seventeen studies meeting the eligibility criteria were included. The pooled prevalence of MetS in AS patients was 15.5% (95% confidence interval [CI]: 10.9–20.8%). The highest prevalence was reported in Africa (37.0%) and the lowest in Asia (8.0%). Variability in AS diagnostic criteria influenced prevalence estimates, with the highest MetS rates found in studies using the Assessment of SpondyloArthritis International Society (ASAS) criteria (37.0%). Meta-regression identified significant associations between MetS prevalence and older age (β = 0.04, P < 0.01), higher body mass index (β = 0.09, P < 0.01), triglyceride levels (β = 0.01, P < 0.01), waist circumference (β = 0.03, P < 0.01), diastolic blood pressure (β = 0.04, P = 0.02) and disease activity, measured by the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) (β = 0.03, P = 0.02). Erythrocyte sedimentation rate was significantly correlated with MetS prevalence (β = 0.01, P = 0.04), while C-reactive protein was not (β = -0.01, P = 0.12). Conclusion MetS is a prevalent comorbidity in AS, significantly influenced by inflammation, obesity, and disease activity. Given its strong association with cardiovascular risk, routine metabolic screening should be incorporated into AS management. Clinicians should adopt an integrated approach that includes lifestyle modifications, targeted therapies, and careful cardiovascular risk assessment to mitigate long-term complications. Standardized diagnostic criteria for MetS in AS are needed to improve risk stratification and patient outcomes.